TECTONO-STRATIGRAPHIC DEVELOPMENT OF THE INTRACRATONIC MALAY BASIN: CORRELATION OF DEFORMATION SCALE AND HYDROCARBON DISTRIBUTION - MANSOR, MD YAZID (2015)
Analyses of regional tectonic data, stratigraphic and basin scale seismic data have allowed a new tectono-stratigraphic framework for the Malay Basin to be proposed. The Malay Basin oil and gas production has been instrumental to the Malaysian economy since early 1980s. However, lately its discovered hydrocarbon resource base is fast depleting. To replenish the draining supply means finding more Tapis-type crude prospects which require new thinking, research and insight.